2003
DOI: 10.1155/2003/304095
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Negative and Dysexecutive Syndromes in Schizophrenia: A Cross‐Cultural Study

Abstract: This paper examined the relationship between the ‘negative syndrome’ (NS) and the neuropsychological ‘dysexecutive syndrome’ (DES) in schizophrenia. The study also examined whether any relationship that exists between the NS and the DES holds equally for British and Japanese subjects. We compared 26 Japanese with 17 British schizophrenic patients, divided into ‘mild’ and ‘severe’ NS groups, on the basis of performance on neuropsychological tests, including the ‘Behavioural Assessment of Dysexecutive Syndrome’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…The visuospatial executive planning ability, measured with the Key Search Test (KST), failed to show a deficit in FES subjects. Impairment in KST was previously demonstrated in studies of chronic SZ (Evans et al, 1997 ; Ihara et al, 2003 ; Vargas et al, 2009 ). The fact that we evaluated first psychotic episode of schizophrenia spectrum patients in early remission could explain this contradictory finding.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The visuospatial executive planning ability, measured with the Key Search Test (KST), failed to show a deficit in FES subjects. Impairment in KST was previously demonstrated in studies of chronic SZ (Evans et al, 1997 ; Ihara et al, 2003 ; Vargas et al, 2009 ). The fact that we evaluated first psychotic episode of schizophrenia spectrum patients in early remission could explain this contradictory finding.…”
Section: Discussionmentioning
confidence: 67%
“…The fact that we evaluated first psychotic episode of schizophrenia spectrum patients in early remission could explain this contradictory finding. Ihara et al ( 2003 ) showed connection between the KST performance and the severity of negative symptoms in chronic SZ subjects. The mild severity of negative symptoms in our FES group could be responsible for the lack of significance found in KST.…”
Section: Discussionmentioning
confidence: 99%
“…While the use of the BADS‐C has not yet been reported in the literature, the adult version of the test has been utilized with a range of patient populations. The BADS therefore appears to be sensitive at detecting executive dysfunction in schizophrenic patients [Cools, Brouwer, de Jong, & Slooff, 2000; Evans, Chua, McKenna, & Wilson, 1997; Ihara, Berrios, & McKenna, 2000, 2003; Katz, Tadmor, Felzen, & Hartman‐Maeir, 2007; Krabbendam, de Vugt, Derix, & Jolles, 1999], drug users [Verdejo‐Garcia & Perez‐Garcia, 2007; Zakzanis & Young, 2001], chronic alcoholics [Moriyama et al, 2002], patients with depression [Paelecke‐Habermann, Pohl, & Leplow, 2005], patients with Parkinson's disease [Kamei et al, 2008] patients with Alzheimer's disease [Amanzio, Geminiani, Leotta, & Cappa, 2008] and patients with traumatic brain injury [Bach, Happé, Fleminger, & David, 2006; Bennett, Ong, & Ponsford, 2005a,b]. Most of the subtests also appear to have good test‐retest reliability [Jelicic, Henquet, Derix, & Jolles, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last century, the neuroscience of SCZ has developed on various research pathways in parallel, evaluating other ideas for the etiology of the disease, from mental symptoms to a theory of mind and social cognition [ 3 ]. Nowadays, we know the brain substrates of both positive and negative symptoms in patients with SCZ.…”
Section: Introductionmentioning
confidence: 99%